2006
DOI: 10.1111/j.1399-3054.2006.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of selenium tolerance mechanisms in Arabidopsis thaliana

Abstract: To investigate selenium tolerance mechanisms in Arabidopsis thaliana, genetic and physiologic studies were performed in the three Arabidopsis accessions Landsberg erecta (Ler), Columbia (Col) and Wassilewskija (Ws). Accession Ler was significantly less tolerant to selenate than Ws and Col, whereas Ws was less tolerant to selenite than the others. Analysis of selenium tolerance in F 1 and F 2 plants obtained from crosses between these accessions suggest that multiple genes are involved in selenate tolerance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…Thus, Ws-2 is more susceptible to selenite than Col-0. These results confirm the report by Zhang et al (2006a) that an Arabidopsis Col accession was more resistant to selenite than Ws. The difference in tolerance index was most pronounced (2-fold) when plants were grown on medium containing 15 or 20 mM selenite, and 15 mM was chosen for all subsequent experiments.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Thus, Ws-2 is more susceptible to selenite than Col-0. These results confirm the report by Zhang et al (2006a) that an Arabidopsis Col accession was more resistant to selenite than Ws. The difference in tolerance index was most pronounced (2-fold) when plants were grown on medium containing 15 or 20 mM selenite, and 15 mM was chosen for all subsequent experiments.…”
Section: Resultssupporting
confidence: 83%
“…The cellular mechanisms regulating ROS production in response to Se in plants are not clear at this point and will require further study. In this context, it is interesting to note that Zhang et al (2006a) showed that a molecular marker on chromosome 4 (ciw7) appeared to be linked to selenite resistance in Col. Although no ethylene-or JA-related gene is found around the marker, a potential defense-related gene, LSD1-like 2 (LOL2; At4g21610), is located close to the marker.…”
Section: Optimal Levels Of Ros Are Necessary For Selenite Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…2A). It is possible that other classes of selenate-resistant mutants could still be found, as indicated by the quantitative trait loci (QTL) study that identified QTLs for selenate resistance that were independent of any sulfate transporter (Zhang et al, 2006a(Zhang et al, , 2006b). The fact that in these last studies no identified QTL actually included sultr1;2 does not in any way cast doubt on our results; it merely confirms the fact that different selection criteria (or different definitions of selenate resistance) may lead to the identification of different classes of mutants and genes.…”
Section: Discussionmentioning
confidence: 99%
“…The element selenium (Se) is an essential micronutrient for many organisms, including mammals. In these organisms Se is incorporated into essential selenoproteins, some of which have antioxidant functions and may help prevent a variety of cancers (Burke, 2002; Zhang et al. , 2006c).…”
Section: Introductionmentioning
confidence: 99%